Central Neurocytoma in a Teenager, a Rare Cause of Hemiplegia, and a Diagnostic Dilemma in a Resource-Poor Setting - Kofi Ulzen-Appiah; Kafui P. Akakpo (Case Reports in Pathology)
Background. Central neurocytoma is a benign intraventricular neuroectodermal tumor most often arising in the lateral ventricles. Due to the location of this tumor, common signs and symptoms include obstructive hydrocephalus, recurrent headache, visual impairment, nausea, and vomiting. Central neurocytoma and intraventricular oligodendroglioma share similar gross features and cellular and architectural morphology, which may pose a diagnostic challenge in a poor resource setting. Immunohistochemical neuronal stains are useful for the two tumors in our setting. Report. An 18-year-old male patient presented with a 1-year history of right-sided weakness, recurrent seizures, and sudden loss of consciousness. The patient showed signs of increased intracranial pressure, but an antemortem CT or MRI scan could not be done to determine the underlying cause, due to lack of availability and poor prognosis of the patient at the time of presentation. An autopsy revealed a well-demarcated solid cystic, gritty intraventricular tumor causing obstructive hydrocephalus, with associated dilated ventricles and severe cerebral edema. Postmortem histopathological examination of the tumor confirmed central neurocytoma. Conclusion. Central neurocytoma (CN) is an uncommon cause of intracranial space occupying lesion (ICSOL) in the teenage age group in our setting. Central neurocytoma and intraventricular oligodendroglioma share similar radiologic and histomorphological features. Immunohistochemical evaluation with neuronal markers is essential in these two tumors, as they have different prognoses and surgical and treatment outcomes.